Effect of tensor nucleon-nucleon forces on the nucleon-nucleus optical potential - Kravchenko, S.M. (Вопросы атомной науки и техники, 2013)
In the approximation of unpolarized nuclear matter, the optical potential for nucleon-nucleus scattering is calculated on the basis of the effective Skyrme interaction with allowance for tensor nucleon-nucleon forces. It is shown that the tensor Skyrme forces make a significant contribution to the imaginary part of the optical potential. The effect of tensor nucleon-nucleon forces on the radial distribution of the imaginary part of the optical potential is investigated by considering the example of elastic neutron scattering by ⁴⁰Ca nuclei at scattering energies of about a few tens of megaelectronvolts. У наближеннi неполяризованої ядерної матерiї розрахований оптичний потенцiал нуклон-ядерного розсiяння на основi ефективної взаємодiї Скiрма з урахуванням тензорних нуклон-нуклонних сил. Доведено, що тензорнi сили Скiрма дають iстотний внесок в уявну частину оптичного потенцiалу. Наприкладi пружного розсiяння нейтронiв ядрами ⁴⁰Ca дослiджено вплив тензорних нуклон-нуклонних сил на радiальний розподiлу явної частини оптичного потенцiалу при енергiях розсiяння в декiлька десяткiв мегаелектронвольт. В приближении неполяризованной ядерной материи рассчитан оптический потенциал нуклон-ядерного рассеяния на основе эффективного взаимодействия Скирма с учетом тензорных нуклон-нуклонных сил. Показано, что тензорные силы Скирма дают существенный вклад в мнимую часть оптического потенциала. На примере упругого рассеяния нейтронов ядрами ⁴⁰Ca исследовано влияние тензорных нуклон-нуклонных сил на радиальное распределение мнимой части оптического потенциала при энергиях рассеяния в несколько десятков мегаэлектронвольт.